Comportamiento agronómico del cultivo de la remolacha forrajera (Beta vulgaris L.) bajo la aplicación de tres bioestimulantes orgánicos, en el cantón Espejo- provincia del Carchi - Chauca Guerrero, Patricio Alexander (2012)
In 2011, a plot of land Chauca Guerrero family located in the area of Jesus del Gran Poder, Parish, La Libertad, Canton Espejo, Carchi Province, located 3100 m living in an area called Lower Montane rainforest, we performed this experiment in order to evaluate the agronomic performance of fodder beet (Beta vulgaria L.) variety brigadier, under the application of organic bio-stimulants among types. The treatments for each bio-stimulant in different doses were, I manure in doses of 2, 3 and 5 L; biol in doses of 2, 3 and 5 L; fruit tea in doses of 0.1, 0.15 and 0.25 L, and compared with a control not applied. The treatments were evaluated in a randomized complete block design with three replications randomly. Plant height was analyzed at 60 and 90 days after transplantation, number of leaves per plant at 60 and 90 days, days to harvest, weight of tubers, tuber size and vigor of the plants at 90 days, and performance of each plot in kg/ha .Moreover there are physical - chemical analysis of bio-stimulants, and bromatological analysis of tubers, as well as economic analysis. The bio - stimulants were applied by spraying the foliage after 30 days of transplantation. All variables were analyzed statistically; the mean comparison of variables was performed with the Tukey test at 5%.